5 - Illicit Capital Flows and Money Laundering in Botswana: An Institutional Economic Analysis - Mogomotsi, Patricia Kefilwe; Mogomotsi, Goemeone E.J.; Hambira, Wame L. (Africa Development, 2020)
Despite the success story of Botswana’s economy, the country is among other southern African countries that are highly prone to money laundering and illicit financial flows. Botswana has been regarded as one of the global conduits for illicit economic activities. Approximately US 1.1 billion and US 1.2 billion illicit financial flows were recorded in 2004 and 2013 respectively. However, there is a dearth of literature on the illicit financial flows in Botswana that takes into account the peculiar institutions, transactions and markets in Botswana. This study therefore aims to contribute to the body of literature by using document analysis and an institutional approach to analyse illicit financial flows in Botswana. The results show that over the years, tremendous efforts have been made to respond to money laundering and related offences. However, some deficiencies still remain. It is essential for financial institutions to carry out remedial exercises in their customer due diligence data in order for them to have useful profiles for risk management purposes. Furthermore, inter-agency co-operation and co-ordination should be enhanced and promoted in order to combat illicit capital flows and money laundering.